'English or Swedish please, no Dari!' – (trans)languaging and language policing in upper secondary school's language introduction programme in Sweden. Issue 3 (2nd October 2019) - Gynne, Annaliina
ABSTRACT: This article examines multilingual interactions in an upper secondary Language Introduction Programme (LIP) classroom in Sweden. The LIPs, highly affected by both glocal linguistic and cultural diversity and the monolingual-monocultural habitus of the surrounding society, offer recently arrived immigrant youth (ages 16–19) education where emphasis is on the majority language of the surrounding society, Swedish, but where teaching can also include other subjects. The study stems from a larger ethnographically framed project, which aims at both creating new knowledge on translanguaging as a pedagogical practice as well as contributing to school development. The paper has a threefold focus. First, it examines everyday multilingual languaging among the participants. Second, it discusses their doing of language policy from a practiced perspective. Third, it reflects upon the implementation process of translanguaging as a pedagogical practice. Data in the study includes video and audio recordings of classroom interactions, fieldnotes, literacy and interview data. Micro-analyses of interactional data are employed in order to discuss the ways in which students and teachers engage in (trans)languaging and language policing processes. Finally, the tension between seeking to teach and learn through linguistic diversity and participants' understandings of what kind of languaging is appropriate is critically reflected upon.